Machinery's Handbook 29th Edition Large Print - Oberg, Erik (Industrial Press, Incorporated, 2012)
Annotation A comprehensive and practical tool, providing its users with the most fundamental and essential aspects of sophisticated manufacturing practice.
Keywords: elektronické knihy; electronic books